PB-SR-ND ISOTOPIC SYSTEMATICS OF MANTLE SOURCES OF POTASSIC ULTRAMAFIC AND MAFIC ROCKS IN THE NORTH OF THE EAST EUROPEAN PLATFORM - Kononova V.A.; Levsky L.K.; Pervov V.A.; Ovchinnikova G.V.; Bogatikov O.A. (My University, 2002)
Pb-Sr-Nd isotopic compositions determined for potassic ultramafic and mafic rocks from some localities in the north of the East European platform characterize compositionally variable magma sources. Kimberlites of the Kepina field have negative εSr (-11.6; -1.2), positive εNd (+1.7; +1.2), and high 206Pb/204Pb 18.46-19.03, 207Pb/204Pb 15.53-15.65, and 208Pb/204Pb 38.43-38.77. They are close in isotopic compositions to the South Africa group I kimberlites and probably correspond to the isotopic composition of an asthenospheric source. Kimberlites of the Zolotitsa field have only negative εNd values (up to -5) with relatively low εSr values (-4.5 to +29) and lower radiogenic Pb isotopic composition: 206Pb/204Pb 18.13-18.27, 207Pb/204Pb 15.50-15.60, 208Pb/204Pb 37.69-38.14. According to these data, their composition is contributed by an ancient enriched mantle source of EMI type, which is most distinctly pronounced in alkali picrites of the Izhmozero field. The latter have the lowest εNd values (-8.8 to -9.5) and lowest 206Pb/204Pb 17.65-17.93, 207Pb/204Pb 15.57-15.76, 208Pb/204Pb 37.89-38.03 and probably are most closely correspond to the composition of the ancient enriched lithospheric mantle of EMI type in this region. Judging by the Nd model age, the mantle enrichment occurred earlier than 2.1 Ga. Kimberlites of the Middle Timan also have the asthenospheric source. However, the U-Pb and Th-Pb systems of these rocks were disturbed and, probably, a part of Pb was lost. According to the high LREE concentrations and εSr (+ 19 to +30) and εNd (up to -9.3) values, the Kostomuksha lamproites were derived from EMI mantle reservoir strongly enriched in LREE due to addition of the lower crustal material. The source of the potassic mafic rocks of the northwestern Ladoga area was close to CHUR in the Sr and Nd isotopic compositions. Their enrichment in LREE probably was coeval with the rearrangement of the U-Pb system (model age T(Nd)CHUR is about 1.8 Ga), i.e., it was close to the rock emplacement time. The probable causes of variations in the isotopic compositions of the rockstudied are also discussed.